2014
DOI: 10.1007/s40266-014-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab, Verteporfin Photodynamic Therapy or Observation for the Treatment of Myopic Choroidal Neovascularization: Cost Effectiveness in the UK

Abstract: PurposeThe aim of this study was to evaluate the cost effectiveness of ranibizumab compared with verteporfin photodynamic therapy (vPDT) or no treatment (observation) in patients with visual impairment due to myopic choroidal neovascularization (CNV).MethodsA Markov model with health states defined by best-corrected visual acuity and a 3-month cycle length was developed. It had a healthcare provider (UK National Health Service and personal social services) perspective, a lifetime time horizon, and was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…In addition, a change of ten letters or more is considered clinically meaningful [28] and is consistent with the secondary end point in the ocriplasmin clinical trial program [2,3]. Blindness was represented by a letter count of ≤35 letters in the better-seeing eye (BSE; VA7 and VA8, Figure 1), consistent with other economic models in ophthalmology [29] and studies that have estimated costs associated with severe vision loss [30,31]. This state-transition model was structured as a partitioned vision distribution model such that each disease health state was associated with a unique distribution of VA categories 1-8 (Figure 2), represented by a beta distribution with parameters estimated from the OASIS trial BCVA data.…”
Section: Partitioned Vision Distribution (Visual Acuity Distribution Within Health States)supporting
confidence: 54%
“…In addition, a change of ten letters or more is considered clinically meaningful [28] and is consistent with the secondary end point in the ocriplasmin clinical trial program [2,3]. Blindness was represented by a letter count of ≤35 letters in the better-seeing eye (BSE; VA7 and VA8, Figure 1), consistent with other economic models in ophthalmology [29] and studies that have estimated costs associated with severe vision loss [30,31]. This state-transition model was structured as a partitioned vision distribution model such that each disease health state was associated with a unique distribution of VA categories 1-8 (Figure 2), represented by a beta distribution with parameters estimated from the OASIS trial BCVA data.…”
Section: Partitioned Vision Distribution (Visual Acuity Distribution Within Health States)supporting
confidence: 54%
“…Indeed, the 1-year results from the VIEW 1 and VIEW 2 studies showed that in the treatment of CNV due to AMD, aflibercept was non-inferior under similar dosing regimens to ranibizumab. 24 , 25 , 26 , 27 , 28 Here, aflibercept maintained the visual gains obtained in the first year of the study with significantly fewer injections compared with ranibizumab.…”
Section: Discussionmentioning
confidence: 62%
“…This factor, in conjunction with treatment-related cumulative damage to the photoreceptors and the underlying retinal pigment epithelium, might compromise the long-term results, as underlined by the relatively few aflibercept injections needed in the present study. Several studies 24 , 25 , 26 , 27 and an open-label, non-comparative phase II trial known as REPAIR (Ranibizumab for the trEatmentof CNV secondary to pathological myopia; an Individualised Regimen) 28 , 29 have shown beneficial results of intravitreal ranibizumab for myopic CNV. Twelve-month data from the phase II study indicated that ranibizumab was associated with significant improvements of BCVA score and central macular thickness.…”
Section: Discussionmentioning
confidence: 99%
“…All costs are quoted in US dollars ($). Conversion rate used was Euro to USD = 1:1.12 ( 22 , 27 ) and Pound sterling to USD = 1:1.31 ( 28 ), using average 2019 exchange rates ( 29 ).…”
Section: Sources and Methods Of Literature Searchmentioning
confidence: 99%